The Most Important Animal of All - Worms, Penny; Bailey, Hannah (Mendota Heights, Minnesota : Jolly Fish Press, 2023)
"When seven children are asked about which is the most important animal of all, they learn about the key roles different animals play on Earth"--
Keywords: Animals -- Fiction; Picture books